2017
DOI: 10.5897/jmpr2016.6285
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive rich extracts from Terminalia ferdinandiana by enzyme-assisted extraction: A simple food safe extraction method

Abstract: A food grade compatible enzyme assisted extraction (EAE) technique for extracting bioactive compounds from freeze-dried Kakadu plum puree was evaluated. To optimise the extraction, a central composite rotatable design (CCRD) was conducted and effects of solvent concentration, enzyme concentration and time of reaction on extracted levels of free ellagic acid (fEA), ascorbic acid (AA) and total phenolic content (TPC) were determined. In the extracts, concentration of fEA ranged from 53.6 to 266.6 mg/100 g dry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Terminalia ferdinandiana (Kakadu plum) is a native Australian fruit consumed by Indigenous communities for centuries. In recent years, T. ferdinandiana has been established as a rich source of antioxidants and other biologically active compounds (1)(2)(3). Commercial demand for T. ferdinandiana fruit continues to increase because of its high vitamin C content (2).…”
Section: Introductionmentioning
confidence: 99%
“…Terminalia ferdinandiana (Kakadu plum) is a native Australian fruit consumed by Indigenous communities for centuries. In recent years, T. ferdinandiana has been established as a rich source of antioxidants and other biologically active compounds (1)(2)(3). Commercial demand for T. ferdinandiana fruit continues to increase because of its high vitamin C content (2).…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid isolated from Ferula foetida , which is a perennial herb, has shown anticancer activity against various types of cancers such as colon and lung cancer, and central nervous system tumors previously [ 27 ]. Additionally, studies have also demonstrated cytotoxicity of flavonoids against cancer cells and have found them to also have high free radical scavenging activity [ 28 ]. Purified flavonoids have shown anticancer activities against a number of human carcinomas which include hepatoma (Hep-G2), cervical carcinoma (Hela), and breast cancer (MCF-7) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies have also demonstrated cytotoxicity of flavonoids against cancer cells and have found them to also have high free radical scavenging activity [ 28 ]. Purified flavonoids have shown anticancer activities against a number of human carcinomas which include hepatoma (Hep-G2), cervical carcinoma (Hela), and breast cancer (MCF-7) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%